A cidade de São Luís-MA como inspiração e lugar de experiência para a aprendizagem musical no Ensino Fundamental II - SALES, Rogério Chaves de (2023)
This present work aims to discuss and propose a view of the city as a space for individual and collective experiences, for music teaching and learning, for artistic activities and for the democratization of cultural assets, which provide an artistic- pedagogical and emancipatory praxis for the local community. The justification for the research is based on the many challenges of the teaching work in music education, such as the new educational guidelines that propose local and global cultural diversity; the valorization of Brazilian aesthetic and cultural matrices; and, notably, the lack of specialized didactic-pedagogical material for elementary school, on the musicalities typical of the city of São Luís-MA. This work starts with a conceptual theoretical foundation based on the thoughts of: Murray Schafer (1999), Marcos Napolitano (2005), Maura Pena (2010), Moacir Gadotti (2005), among others. Regarding the curricular guidelines for Art, we analyzed the Curricular Document of the Maranhense Territory, reinforced by the national regulations (LDB, PCN, BNCC etc.), the theme of experience in John Dewey (2010) and the studies that propose the cultural and musical diversity like the Lucy Green (2012) project. The methodology adopted was bibliographic and documentary research, physical and virtual (publications, periodicals, academic research, internet sites, critical analysis, images and other audiovisual media), on artists, groups, musical works and cultural spaces in the city, and also the musical genres (baião, bumba meu boi, reggae) and style (MPM), aiming to investigate historical, social and cultural data, about their origins and current events, considering the subjectivities, relationships, values and cultural experiences demanded by society from São Luís. Finally, we point out a systematized, reflective and contextualized proposal of musical teaching methodology, which includes conceptualizations and exercises on some musical aspects and elements.